Identification of durum wheat cultivars and their tetraploid relatives with low cadmium content - Tekin, Mehmet; Cat, Ahmet; Sönmez, Sahriye; Akar, Taner (2020)
In this study, 71 durum wheat cultivars (Triticum durum Desf.), 22 emmer wheat (Triticum dicoccum L.) and 11 wild emmer (Triticum dicoccoides L.) genotypes were genetically characterized to determine the alleles associated with high cadmium (Cd) content. After genotypic characterization, 14 cultivars selected among all genotypes with low and high Cd content were phenotyped by a pot experiment to verify the genotypic data. Identification of 32 durum wheat, one emmer wheat and four wild emmer genotypes showed that they have alleles associated with high Cd content, while 68 genotypes of which 39 durum wheat, 21 emmer wheat and 7 wild emmer cultivars had alleles associated with low Cd content. Moreover, phenotypic data obtained from pot experiment were similar to the molecular data. To sum up, the marker successfully classified durum wheat cultivars into either high or low accumulators and these results can be safely used in breeding programs to improve new durum wheat cultivars with alleles associated with low Cd content. Due to routine use of phosphorus fertilizers in agricultural areas and other anthropogenic factors related to Cd toxicity, new durum wheat cultivars with low Cd content should be urgently developed for safe production of macaroni or other types of wheat products for human and animal consumption.
U ovom su radu okarakterizirani genotipovi 71 kultivara tvrde pšenice (Triticum durum Desf.), 22 kultivara dvozrnca (Triticum dicoccum L.) i 11 kultivara divlje dvozrne pšenice (Triticum dicoccoides L.) u svrhu pronalaska alela povezanih s većim udjelom kadmija. Nakon toga je uzgojem u posudi ispitan fenotip 14 odabranih kultivara s malim i velikim udjelom kadmija, radi potvrde genotipskih podataka. Identificirana su 32 genotipa tvrde (durum) pšenice, jedan kultivar dvozrnca i četiri kultivara divlje dvozrne pšenice koji sadržavaju alele povezane s velikim udjelom kadmija, te 68 genotipova koji sadržavaju alele povezane s malim udjelom kadmija, i to 39 kultivara durum pšenice, 21 dvozrnca i 7 divlje dvozrne pšenice. Povrh toga, fenotipske karakteristike uočene nakon uzgoja u posudama potvrdile su rezultate molekularne analize. Marker je uspješno upotrijebljen za klasifikaciju kultivara durum pšenice u one s velikim ili malim udjelom kadmija, pa je zaključeno da se može upotrijebiti u programu uzgoja novih kultivara durum pšenice koja sadržava alele povezane s malim udjelom kadmija. Zbog rutinske primjene fosfornih gnojiva na poljoprivrednim površinama i utjecaja ostalih antropogenih čimbenika što dovode do akumulacije toksičnog kadmija, treba čim prije razviti nove kultivare durum pšenice s malim udjelom kadmija za sigurnu proizvodnju makarona i ostalih tipova pšeničnih proizvoda za prehranu ljudi i ishranu stoke.
Bibliografija: 28 jed.
Summary ; Sažetak.
Keywords: Durum pšenica -- Tetraploidna pšenica -- Kadmij -- Pšenični proizvodi